Sacrifice and modern war literature : from the battle of Waterloo to the War on Terror - Houen, Alex; Schramm, Jan-Melissa (Oxford University Press, 2018)
This book explores how writers from the early nineteenth century to the present have addressed the intimacy of sacrifice and war. Each chapter presents fresh insights into the literature of a particular conflict. The range of literature examined complements the rich array of topics related to wartime sacrifice that the contributors discuss.